A Humanist Diplomat in Early 16th Century Hungary: Hieronymus Balbus - Bárány, Attila (Acta Neerlandica, 2020)
The article investigates new sources, Western European, mainly English diplomatic reports – several being so far unknown for Hungarian scholarship, or, if known, not examined in this regard – e.g. held at the British Library Manuscript Collection to shed light on Hungarian-Ottoman relations at the eve of the fall of the “shield of Christendom”, Belgrade in 1521. The article follows the mission of Hieronymus Balbus, an Italian at the diplomatic personnel of Jagiellonian Hungary, in 1521 to the Habsburg, Tudor and Valois courts. Balbus’s diplomatic workings – through the embassy to the Emperor (Charles V in Worms and Brussels), a peace conference at Calais and Cardinal Wolsey and Henry VIII, King of England – has not been adequately seen in Hungarian historiography, and some of his letters and political activity ranging from Bruges, Worms, Calais, London and Cologne has not so far been mapped, yet new insights can be given for the understanding of Louis II’s diplomatic efforts during the stress of the siege and loss of Belgrade in 1521. The investigation is largely based on Balbus’s dispatches – which has not survived in Hungarian archival material but were preserved in the reports of English envoys of his activity, to the maker of Tudor policy, Chancellor Wolsey. The correspondence of Balbus provides valuable information on the administration of Louis II, about its relationship with the Turks and the Emperor. The leaders of Hungarian diplomacy did not lack astuteness and “had a clear picture” about the international power relations. The government experimented with alternatives, provided they did not receive any aid from the Habsburgs: they were willing to go as far as making an alliance with not only the English, but even with the Emperor’s enemies, the Valois. In 1521, despite the powerful Habsburg dominance, Hungarian foreign politics did have some room to manoeuvre.